La riflessione critica di Renato Rozzi tra soggettività, storia e società (Materiali di Estetica. Terza serie, 2025)
In the article, the author talks about his relationship with the man and his work. Interested in social history, he favors this aspect of the master's manifold activity, being the prevailing topic of their long common dialogue. In the narrative, the author highlights Rozzi's fidelity to some fundamental values, his passion for social sciences, particularly for depth psychology, as well as his original methodological framework, focusing on some significant results of his socio-historical analysis concerning the peasant and worker worlds, the destructiveness of labor, and the contemporary history of his city. He also details Renato Rozzi's critique of the traditional rural world's subordination, his explanation of the profound causes of the Fordist factory workers' uprising, his proposal of a new idea of human labor, and his aspirations for a more open urban society.
Keywords: Renato Rozzi; psicologia; lavoro; memoria